Bazedoxifene exhibits growth suppressive activity by targeting interleukin‐6/glycoprotein 130/signal transducer and activator of transcription 3 signaling in hepatocellular carcinoma. Issue 3 (16th February 2019) - Ma, Haiyan; Yan, Dan; Wang, Yina; Shi, Wei; Liu, Tianshu; Zhao, Chongqiang; Huo, Shengqi; Duan, Jialin; Tao, Jingwen; Zhai, Maocai; Luo, Pengcheng; Guo, Junyi; et al.
Abstract : The interleukin (IL)‐6/glycoprotein (GP)130/signal transducer and activator of transcription (STAT)3 pathway is emerging as a target for the treatment of hepatocellular carcinoma. IL‐6 binds to IL‐6R, forming a binary complex, which further combines with GP130 to transduce extracellular signaling by activating STAT3. Therefore, blocking the interaction between IL‐6 and GP130 may inhibit the IL‐6/GP130/STAT3 signaling pathway and its biological effects. It has been reported that bazedoxifene acetate (BAZ), a selective estrogen receptor modulator approved by the US Food and Drug Administration, could inhibit IL‐6/GP130 protein‐protein interactions. Western blot, immunofluorescence staining, wound healing and colony formation assays were used to detect the effect of BAZ on liver cancer cells. Cell viability was evaluated by MTT assay. Apoptosis of cells was determined using the Annexin V‐FITC detection kit. Mouse xenograft tumor models were utilized to evaluate the effect of BAZ in vivo. Our data showed that BAZ inhibited STAT3 phosphorylation (P‐STAT3) and expression of STAT3 downstream genes, inducing apoptosis in liver cancer cells. BAZ inhibited P‐STAT3 induced by IL‐6, but not by leukemia inhibitory factor. BAZ inhibited P‐STAT1 and P‐STAT6 less significantly as elicited by interferon‐α, interferon‐γ and IL‐4. In addition, pretreatment of BAZ impeded the translocation of STAT3 to nuclei induced by IL‐6. BAZ inhibited cell viability, wound healing and colony formation in vitro. Furthermore, tumor growth in HEPG2 mouse xenografts were significantly inhibited by daily intragastric gavage of BAZ. Our results suggest that BAZ inhibited the growth of hepatocellular carcinoma in vitro and in vivo, indicating another potential strategy for HCC prevention and therapy. Abstract : Bazedoxifene exerted significant inhibitory effects on STAT3 phosphorylation, nuclear translocation and expression of STAT3‐mediated downstream genes in human liver cancer cell lines. Bazedoxifene also showed significant anti‐tumor activity in nude mice implanted with HEPG2 cells.